Effect of severity and etiology of chronic kidney disease in patients with heart failure with mildly reduced ejection fraction - Schupp, Tobias; Weidner, Kathrin; Lau, Felix; Forner, Jan; Schmitt, Alexander; Reinhardt, Marielen; Abel, Noah; Ayasse, Niklas; Bertsch, Thomas; Akin, Muharrem; Weiß, Christel; Akın, Ibrahim; et al. (Clinical research in cardiology, 2024)
The study investigates the prognostic impact of the severity and etiology of chronic kidney disease (CKD) in patients with heart failure with mildly reduced ejection fraction (HFmrEF).
Online veröffentlicht: 6. Mai 2024
Gesehen am 17.12.2024